2017
DOI: 10.1063/1.4976699
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature insulating ferromagnetism induced by charge transfer in ultrathin (110) La0.7Sr0.3MnO3 films

Abstract: The achievement of high temperature ferromagnetism in perovskite manganites has proved both fundamentally and technologically important for spintronics devices. However, high operating temperatures have not been achieved due to the depression of the Curie temperature and the rapid spin filtering efficiency loss, which are the main obstacles for practical applications. Here, we report unexpected room temperature insulating ferromagnetism in ultrathin (110) oriented La0.7Sr0.3MnO3 (LSMO) films. The relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The most striking finding here is the shift of L 3 peak toward higher energy in comparison with LMO single film. From the published spectra of Mn XAS on La 1−x Sr x MnO 3 , it is known that the shift of the XAS spectrum towards higher energies is mainly due to Mn 4+   22 . Comparison of the published spectra with our data reveals that the (3–3) SL clearly shows more Mn 4+ valence than other two directions of SLs, while the Mn spectral features for (4–4) and (5–5) indicate a valence state between those of LMO and the (3–3) SL.…”
Section: Resultsmentioning
confidence: 99%
“…The most striking finding here is the shift of L 3 peak toward higher energy in comparison with LMO single film. From the published spectra of Mn XAS on La 1−x Sr x MnO 3 , it is known that the shift of the XAS spectrum towards higher energies is mainly due to Mn 4+   22 . Comparison of the published spectra with our data reveals that the (3–3) SL clearly shows more Mn 4+ valence than other two directions of SLs, while the Mn spectral features for (4–4) and (5–5) indicate a valence state between those of LMO and the (3–3) SL.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, LSMO thin films are used as buffer layers in many device structures such as magnetic field sensing, resistive sensor and magnetic storage applications at RT 1,5 . Moreover, differing previous studies on ultrathin (110) oriented LSMO films grown on SrTiO 3 (110) substrates have reported a room temperature insulating magnetic phase depending on thickness, induced by strain, but with ferromagnetic structure with T C ∼330 K for thickness above 15 unit cells 6 or a canted antiferromagnetic structure with higher T C ∼560 K for thickness below the critical value of 10 unit cells 7 . On the other hand, direct silicon-based heterostructures greatly facilitate the fabrication of microelectronic devices.…”
mentioning
confidence: 67%
“…5a. Previous studies on LSMO films grown on dissimilar substrates have reported ZFC curves exhibiting a FM behavior with Curie temperatures between 330 K to 560 K for thin films [5][6][7]24 and 370 K for bulk samples 25 ; but recently, studies on LSMO:CuO nanocomposite films have reported T C values around 220 K and 250 K 26 . The lower value of 218 K here obtained could be correlated with the in-plane misorientation and the inter-nanoregions disordered phase boundaries with random in-plane orientations inherited from the two-dimensional Si-O-Si array at the surface of the native amorphous where the LSMO thin film grew.…”
Section: Magnetic Characterization Figures 5ac Show the In-plane M(mentioning
confidence: 99%
“…The spectra are defined by the energy domains A, B, C, D, and E associated to different transitions from the O 1s core level. The energy range between (528 and 536 eV) corresponds to the transition from O 1s to hybridized states between Mn 3d and O 2p sub-band is influenced by the unoccupied O 2p states. , In particular, the peak A (∼531.4 eV) corresponds to the O 2p hybridized mainly with Mn t 2g orbitals, whereas the hybridization with e g is responsible for the peak at B (∼533.8 eV). The t 2g and e g states show a large splitting because of the octahedral crystal field of 10 D q value ∼2.4 eV.…”
Section: Resultsmentioning
confidence: 99%